2018
DOI: 10.1016/j.molcel.2018.07.020
|View full text |Cite
|
Sign up to set email alerts
|

Argonaute-miRNA Complexes Silence Target mRNAs in the Nucleus of Mammalian Stem Cells

Abstract: In mammals, gene silencing by the RNA-induced silencing complex (RISC) is a well-understood cytoplasmic posttranscriptional gene regulatory mechanism. Here, we show that embryonic stem cells (ESCs) contain high levels of nuclear AGO proteins and that in ESCs nuclear AGO protein activity allows for the onset of differentiation. In the nucleus, AGO proteins interact with core RISC components, including the TNRC6 proteins and the CCR4-NOT deadenylase complex. In contrast to cytoplasmic miRNA-mediated gene silenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
123
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 114 publications
(148 citation statements)
references
References 88 publications
(140 reference statements)
12
123
0
Order By: Relevance
“…Previous studies have demonstrated that 3'-untranslated regions (3'UTRs) of mRNAs are the preferred, although not exclusive, sites of interaction between miRNAs and mRNAs (Bartel, 2018;Chi et al, 2009;Sarshad et al, 2018). Consistent with these findings, the majority of HEAP peaks we identified in mESCs mapped to 3'UTRs, followed by sites mapping to coding exons (Figure 2a, Supplementary Figure 2c).…”
Section: A Halo-ago2 Fusion Protein Enables Antibody-free Purificatiosupporting
confidence: 87%
“…Previous studies have demonstrated that 3'-untranslated regions (3'UTRs) of mRNAs are the preferred, although not exclusive, sites of interaction between miRNAs and mRNAs (Bartel, 2018;Chi et al, 2009;Sarshad et al, 2018). Consistent with these findings, the majority of HEAP peaks we identified in mESCs mapped to 3'UTRs, followed by sites mapping to coding exons (Figure 2a, Supplementary Figure 2c).…”
Section: A Halo-ago2 Fusion Protein Enables Antibody-free Purificatiosupporting
confidence: 87%
“…Human genome encodes four Argonaute proteins, Ago1-4. A recent report shows that Argonaute-miRNA complexes can target mRNAs even in the nucleus of stem cells (Sarshad et al, 2018). Ago proteins interact with miRNAs and siRNAs and load them onto their target mRNAs to silence their expression.…”
Section: Introductionmentioning
confidence: 99%
“…They are highly conserved proteins and found in most eukaryotes (except Saccharomyces cerevisiae). A recent report shows that Argonaute-miRNA complexes can target mRNAs even in the nucleus of stem cells (Sarshad et al, 2018). In addition to their role in small RNA-mediated post-transcriptional gene silencing, human Ago proteins have roles in transcription, splicing, and DNA repair (Meister, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However, there is accumulating evidence that some fraction of mammalian miRNAs may also execute important nuclear regulatory functions by controlling gene expression in the nucleus at both transcriptional and posttranscriptional levels, as well as by affecting alternative splice site selection (Roberts, 2014). In a set of elegant experiments, a significant fraction of miRNAs and several RISC components, including AGOs, have been identified to become located and functionally operative within the nucleus of human cells (Avivi et al, 2017; Bottini et al, 2017; Castanotto et al, 2018; Gagnon, Li, Chu, Janowski, & Corey, 2014; Ohrt et al, 2008; Sarshad et al, 2018; Weinmann et al, 2009). Nuclear localized miRNAs were found capable both to suppress and to stimulate transcriptional expression at distinct gene loci, involving direct and indirect interference pathways.…”
Section: Epigenetic Foundations Of Transcriptional Memorymentioning
confidence: 99%